2022
DOI: 10.3390/cells11081254
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Platelet-Enriched MicroRNAs as Biomarkers of Platelet Activation

Abstract: Dysregulation of platelet function is causally connected to thrombus formation and cardiovascular diseases. Therefore, assessing platelet reactivity is crucial. However, current platelet function tests come with pitfalls, limiting clinical use. Plasma miRNA signatures have been suggested as novel biomarkers for predicting/diagnosing cardiovascular diseases and monitoring antiplatelet therapy. Here, we provide results from a comprehensive study on the feasibility of using circulatory platelet miRNAs as surrogat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Among them, we selected the top ten species based on their abundance in plasma to form the list of potential RBC-derived circulating extracellular miRNAs. Similarly, we selected the top 10 potential platelet-derived miRNA species based on previous studies revealing the presence of platelet-specific miRNAs in extracellular fraction or using small RNA sequencing or microarray screening to analyze platelet miRNome [ 31 , 32 , 33 , 38 ]. Platelet-derived circulating miRNA levels are an important marker of in vivo or in vitro platelet activation resulting in the release of PMVs which contain specific miRNA signatures [ 31 , 33 , 34 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, we selected the top ten species based on their abundance in plasma to form the list of potential RBC-derived circulating extracellular miRNAs. Similarly, we selected the top 10 potential platelet-derived miRNA species based on previous studies revealing the presence of platelet-specific miRNAs in extracellular fraction or using small RNA sequencing or microarray screening to analyze platelet miRNome [ 31 , 32 , 33 , 38 ]. Platelet-derived circulating miRNA levels are an important marker of in vivo or in vitro platelet activation resulting in the release of PMVs which contain specific miRNA signatures [ 31 , 33 , 34 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Plasma preparation conditions may also cause platelet activation and release of platelet microvesicles (PMVs) which contain specific miRNA signatures [ 31 , 32 , 33 , 34 , 35 ]. PMVs constitute the main fraction of all microvesicles in plasma [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Active or passive release from other cell types likely contributes to basal levels. MiR-223-3p and miR-150-5p are also expressed in leukocytes ( de Rie et al, 2017 ; Krammer et al, 2022 ). MiR-126-3p is abundant in endothelial cells, while miR-24-3p shows broad expression among different tissues ( de Rie et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main carrier of extracellular miRNAs remains a matter of controversy and likely differs between miRNAs. We previously reported that basal levels of platelet-related miRNAs are mainly protein-bound ( Krammer et al, 2022 ). Activated platelets have been shown to secrete EVs with miRNAs as cargo ( Diehl et al, 2012 ; Gidlöf et al, 2013 ; Laffont et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation